Socially Responsible Investment - Muñoz Fernández, Alberto (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
Socially responsible investing involves integrating social, environmental or ethical considerations in the investment process without giving up the pursuit of profit. The strategies that can be followed to incorporate these elements are varied. Historically, SRI has evolved from an ethical conduct, to consider that in the long term, taking into account the social, environmental, ethical or governance risks is beneficial for returns on a more sustainable way. It is not surprising that initiatives have arisen from international bodies, the securities sector or investors themselves to promote these practices. Moreover, laws to encourage responsible investment are becoming more frequent.doi: http://dx.doi.org/10.20318/eunomia.2016.3293
Keywords: Socially Responsible Investment; ethical investment; sustainability; Equator Principles; principles for responsible investment; transparency; non financial issues